Mental conditioning and pulse oximetry monitoring in short-term training of alpine skiers aged 13-16 years - Grosu, V. T.; Mancini, N.; Rozsnyai, R. A.; Neagu, S. G.; Monea, D.; Grosu, E. F.; Dobrescu, T.; Hervás-Gómez, C.; Popovici, C. (Pedagogy of Physical Culture and Sports, 2025)
Background and Study Aim: Mental conditioning is an important part of modern athletic preparation. It helps regulate arousal, focus, and performance stability. This study examined the psychophysiological effects of a short mental training routine that combined relaxation and sport-specific imagery in junior alpine skiers.